Rethinking decision-making strategies and tools : emerging research and opportunities - Palazzo, Maria; Micozzi, Alessandra (Emerald Publishing Limited, 2024)
Rethinking Decision-Making Strategies and Tools: Emerging Research and Opportunities analyses established decision-making tools, and on the necessity to re-arrange and re-evaluate some of them. The authors propose a new matrix with eight quadrants of the dynamic SWOT analysis. The new tool also considers three dimensions: (1) Actual - Potential, (2) Positive - Negative and (3) Internal - External. Applications for this revised matrix are offered in a range of relevant case studies, along with examples from a wide range of industries and firms to illustrate the many dimensions of decision-making tools and theories. Readers will be able to compare, contrast and comprehend whether the 'decision making strategies and tools' from different lenses are delivered similarly, or otherwise, in different parts of the world. The text includes an interesting mix of theory, primary research findings, and practice that will appeal to students, academics, and practitioners alike.